Analisis Manajemen Risiko Operasional Pada Rumah Makan Ondo Grill Batak - Br Tarigan, Eli Agustina; Jeni Sinurat; Ibersina Br Ginting; Rossy Pratiwi Sihombing; Putri Kemala Dewi Lubis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the operational risks faced by Rumah Makan Ondo Batak Grill, a famous culinary business on Jl. Weaving Factory No. 45, Sei Putih Tengah, Medan Petisah District, Medan City, North Sumatra. The qualitative method used in this research is data collection techniques by conducting direct observations and interviews with the owner of the Ondo Grill Batak Restaurant. The research results reveal that there are several significant operational risks, including hygiene and food safety risks, equipment damage risks, employee absenteeism risks, and customer number risks. To manage possible risks, Ondo Restaurant has implemented several strategies, such as regular employee training regarding food hygiene and safety, routine maintenance and inspection of cooking equipment, and development of an employee attendance management system. Apart from that, this restaurant is also diversifying its menu and promotions to attract more customers and maintain income stability. This research concludes that effective operational risk management is very important for the survival and success of Ondo Restaurant. The recommendations provided include improving the risk monitoring system and implementing risk management strategies on a regular basis.